Wireless vehicular networks for car collision notifification : basics, concepts, and frameworks - Muhammad Naim Abdullah; Mohd. Afizi Mohd. Shukran; Mohd Sidek Fadzil Mohd Yunus (Penerbit UPNM, 2019)
This book is describes the determining and detecting the occurrence of an accident by monitoring the smart phone acceleration sensor.